2017
DOI: 10.1111/jgs.14871
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Mini‐Mental State Examination in Late Nonagenarians and Its Relationship with Dementia, Mortality, and Education

Abstract: MMSE score is associated with dementia and subsequent mortality even in very old individuals, although the preclinical phase of dementia may be short in older age. Level of education is positively associated with MMSE score but not rate of decline in individuals approaching age 100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
6
18
0
1
Order By: Relevance
“…[10]. In line with reports that cognitive performance is highly correlated with survival in the oldest old [37], we find that the centenarians who score highest on cognitive tests in the ongoing prospective study are underrepresented among the first centenarians in the 100-plus Study who came to autopsy (data no shown). We therefore speculate that individuals with a low burden of pathology might survive until extreme ages, and will come to autopsy at a later time after inclusion.…”
Section: Accumulation Of Neuropathologies Is Common In Centenarianssupporting
confidence: 90%
“…[10]. In line with reports that cognitive performance is highly correlated with survival in the oldest old [37], we find that the centenarians who score highest on cognitive tests in the ongoing prospective study are underrepresented among the first centenarians in the 100-plus Study who came to autopsy (data no shown). We therefore speculate that individuals with a low burden of pathology might survive until extreme ages, and will come to autopsy at a later time after inclusion.…”
Section: Accumulation Of Neuropathologies Is Common In Centenarianssupporting
confidence: 90%
“…In the second year after baseline mortality increased to 28%: specifically, centenarians with high cognitive functioning retained a low mortality of 17%, while centenarians with a decline in cognitive functioning had a mortality rate of 42%. Our results confirm that there is an overlapping etiology of maintained cognitive and overall health, and cognitive functioning might be employed to predict overall decline and mortality [49,50]. The longitudinal set--up of our study will allow us to monitor changes in cognition in combination with other factors of overall health that occur between baseline and death to identify to which extent centenarians escaped or delayed cognitive impairment.…”
Section: Cognitive Performance Is Associated With Mortalitysupporting
confidence: 68%
“…In addition, people who have higher levels of education have healthier lifestyles, less chronic stress, better socioeconomic status, etc, which may contribute to recover from MCI to NC. Education is related to cognitive reserves, and a study indicated that higher education was associated with higher MMSE scores. Gao et al proposed that those with higher MMSE total scores were more likely to revert to NC.…”
Section: Disscusionmentioning
confidence: 99%